iDub - The potential of intralingual dubbing in foreign language learning: How to assess the task - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Author/s Noa Talaván Tomás Costal Universidad Nacional de Educación a Distancia, Spain   ABSTRACT Research on the use of active dubbing activities in foreign language learning is gaining an increasing amount of attention. The most obvious skill to be enhanced in this context is oral production and a few authors have already mentioned the potential benefits of asking students to record their voices in a 'semi-professional' manner. The present project attempts to assess the potential of intralingual dubbing (English-English) to develop general oral production skills in adult university students of English B2 level in an online learning environment, and to provide general guidelines of dubbing task assessment for practitioners. To this end, a group of undergraduate pre-intermediate students worked on ten sequenced activities using short videos taken from an American sitcom over a period of two months. The research study included language assessment tests, questionnaires and observation as the basic data gathering tools to make the results as reliable and thorough as possible for this type of educational setting. The conclusions provide a good starting point for the establishment of basic guidelines that may help teachers implement dubbing tasks in the language class.